Penggunaan Media Pembelajaran Whiteboard Animation dalam Menumbuhkan Keterampilan Abad 21 Mata Pelajaran Al-Qur'an Hadits di MI Assyafi'iyah Keben - M. Yunus; M. Fadlil (STIT Fatahillah, 2023)
This study aims to analyze the use of Whiteboard Animation as a learning medium in teaching Al-Qur'an Hadith to sixth grade students. This study also aims to implement the use of Whiteboard Animation in teaching Al-Qur'an Hadith to develop 21st century skills and analyze its contribution in developing these skills. The research method used is descriptive analytical research with a qualitative approach. The research subjects consisted of teachers and sixth grade students at an Islamic elementary school in Indonesia. The results showed that the use of Whiteboard Animation in teaching Al-Qur'an Hadith can increase students' interest and motivation in learning. This media provides a more interesting and interactive learning experience, so that students are more active and involved in the learning process. Besides that, using Whiteboard Animation can also help sis.